Variability in the abundance and species composition of diatoms in sinking particles in the northern South China Sea: Results from time-series moored sediment traps. (December 2015) - Ran, Lihua; Chen, Jianfang; Wiesner, Martin G.; Ling, Zheng; Lahajnar, Niko; Yang, Zhi; Li, Hongliang; Hao, Qiang; Wang, Kui
Abstract: Seasonal variability of diatom abundance and species composition in sinking particles in the northern South China Sea was studied using continuous time-series sediment trap moorings during a one-year period, 2009–2010. A clear seasonal pattern of diatom abundance was observed, with higher fluxes in winter than in summer. This could be related to positive response of diatom growth to increased nutrient supply from the subsurface waters as a result of enhanced vertical mixing in winter. Mesoscale eddy activities and strong Asian dust input could also stimulate the diatom growth and increase the diatom export flux to the deep South China Sea. The strong Asian dust input during spring 2010 probably accelerated the aggregation and downward flux of diatoms in the northern South China Sea. No distinctive seasonal pattern in diatom species composition was recorded, but there was a close correlation of diatom abundances with the cell size and the degree of silification. The sinking velocity of the diatom related particles from the sea surface to the deep South China Sea has been estimated to be ~30–50 m d −1 by comparing the surface chlorophyll a with the diatom abundance and species in sediment traps at 1003 m and 3226 m depths. Strong dissolution of small-sized and low-silicified diatom species and lateral advection of particles were also indicated for the deep northern South China Sea. The present results are crucial as a basis for future understanding of fossil assemblage changes in connection with palaeoclimatic and palaeooceanographic research.